Path-dependent Vortex Switching in Ferroelectric Nanoplate Junctions Toward a Memory Device Concept - Xiong, Weiming; Chen, Weijin; Zheng, Yue (Frontiers in Physics, 2022)
Ferroelectric vortex has attracted much attention as a promising candidate for memories with high density and high stability. It is a crucial problem to precisely manipulate the vortex chirality in order to utilize it to store information. Nevertheless, so far, a practical and direct strategy for vortex switching is still lacking. Moreover, the strong coupling of chirality between neighboring vortices in continuous systems like superlattices limits the application of ferroelectric-vortex-based memories. Here, we design a ferroelectric nanoplate junction to break the strong coupling between neighboring vortices. Phase-field simulation results demonstrate that the vortex chirality of the nanoplates could be efficiently tuned by sweeping local electric and thermal fields in the nanoplate junction. More importantly, the weak coupling between two neighboring nanoplates through the intermediate junction brings a deterministic vortex switching behavior. Based on this, we propose a concept of vortex memory devices. Our study provides an effective way to control the vortex chirality and suggests an opportunity for designing new memory devices based on ferroelectric vortex.